DRG FOCUS: A Multicenter Study Evaluating Dorsal Root Ganglion Stimulation and Predictors for Trial Success. Issue 1 (7th August 2018) - Hunter, Corey W.; Sayed, Dawood; Lubenow, Timothy; Davis, Timothy; Carlson, Jonathan; Rowe, Jeffery; Justiz, Ralph; McJunkin, Tory; Deer, Timothy; Mehta, Pankaj; Falowski, Steven; Kapural, Leo; et al.
Abstract : Introduction: Dorsal root ganglion stimulation (DRGS) is a powerful tool in the treatment of chronic, neuropathic pain. The premise of DRGS is similar to that of conventional spinal cord stimulation (cSCS), however, there is more variability in how it can be utilized. While it is this variability that likely gives it its versatility, DRGS is not as straightforward to implement as cSCS. The purpose of this study was to assess the efficacy of DRGS on a broad number of diagnoses, determine which dorsal root ganglia were associated with better outcomes for particular body parts/diagnoses, and evaluate what factors/parameters were associated with higher rates of trial success. Methods: This is a physician initiated, multicenter retrospective registry of 217 patients trialed with DRGS. Data were collected via an online questionnaire that assessed specifics regarding the patient's pain, distribution, size, and response to treatment. The data were analyzed to see if there were certain diagnoses and/or parameters that were more or less associated with trial success. Results: DRGS was found to be an effective treatment in all diagnoses evaluated within this study, most of which had statistically significant improvements in pain. The most important predictor of trial success was the amount of painful area covered by paresthesias during the programing phase. The number of leads utilized had a direct and indirect impact on trial success. Pain in the distribution of a specific peripheral nerve responded best and there was no statistical difference based on what body part was being treated. Conclusion: DRGS can be an effective treatment for a variety of neuropathic pain syndromes, in addition to CRPS. It is recommended that a minimum of 2 leads should be utilized per area being treated. In addition, this therapy was shown to be equally efficacious in any body part/region so long as the area being treated is focal and not widespread.